Behavioral Interventions in Education: A Cluster Randomized Trial of SMS Nudges in Low Income Regions of Indonesia - Yasin, Muhammad (Psychosocia : Journal of Applied Psychology and Social Psychology, 2025)
This study investigates the effectiveness of SMS-based behavioral nudges in reducing school dropout rates in disadvantaged regions of Indonesia. The research addresses persistent educational disparities that remain despite financial aid programs such as BOS and PIP. Inspired by behavioral insights and global practices, the intervention focused on motivational and loss-aversion messages delivered via SMS to parents and students. A cluster randomized trial was implemented in low-income communities in Papua and Sulawesi. The trial compared control and treatment groups by measuring attendance, retention, and parental engagement, with baseline and follow-up data used to capture behavioral changes. Results showed significant improvements in attendance and a modest reduction in dropout rates among the treatment group. Motivational nudges produced stronger effects than neutral reminders, and impacts were amplified when combined with financial aid programs. Supportive parental attitudes also contributed to sustained engagement. The study concludes that SMS-based nudges are a cost-effective and scalable tool to complement existing education policies. Ethical implementation requires attention to consent, privacy, and cultural sensitivity. Future research should focus on long-term behavioral impacts and integration with national education platforms.